(untitled) (Research, Society and Development, 2021)
Objectives: To know the profile of smartphone use and dependence of adolescents in full-time schools. Method: Cross-sectional study carried out in six State Schools of Professional Education (EEEP) in the city of Fortaleza, Ceará, Brazil, developed between September and October 2019. 286 adolescents (15-19 years old) participated who answered two questionnaires (sociodemographic data, use and smartphone dependency). SPSS 23.0 was used for descriptive and inferential analysis, with the outcome being smartphone dependence. Results: There was a higher percentage of males (53.5%), age of 16 years (31.5%) and social class D (52.4%). Regarding usage, 96.2% used to access social networks, 71.0% to receive and make calls, 68.9% to play games and 66.1% to watch movies. It was found that 62.6% had smartphone dependence, with 7.3 (± 3.4) hours / daily use time. An association was found between smartphone dependence and age (OR: 1.48; p=0.009), using headphones (OR: 2.76; p<0.001), and using the smartphone 1h 18 minutes more (p=0.003). Conclusion: Among the reasons for the use of smartphones by teenagers are accessing social networks, watching movies and playing games, as well as using WhatsApp for communication purposes. High dependence and time of smartphone use in adolescents was evidenced, associated with age and the use of headphones. Thus, it warns of the need for educational campaigns and guidance on the conscious use of the smartphone aiming at the prevention and reduction of physical and mental health problems.